Efficient bulk scale synthesis of popular pesticide synthon: tetrachlorothiophene. (3rd July 2017) - Shiva Reddy, G. V.; Chandrappa, M.; Padmanabha Gowda, V. N.; Rahaman, Fazlur; Kumar, S. Girish; Narasimha Murthy, B. N.; Pullela, Phani Kumar
Abstract: Broad spectrum pesticides are molecules which act across a range of pests. The popular class of compounds with this property are thiacloprid, nitenpyram, ethaboxam, silthiofam, 3, 3, 4, 4-tetrachloro tetrahydro thiophene etc. Interestingly, all these compounds possess at least one heterocyclic ring like thiophene, furan, and imidazole etc. in their structure. Among the synthons available for synthesis of neonicotinoids, tetrachlorothiophene is unique. The bulk scale synthesis of tetrachlorothiophene is reported only by cyclization of hexachloro-1, 3-butadiene. The reaction yields of synthesis of this synthon are around 45%. We report silica-coated magnetic nanoparticles as a generic catalyst for this cyclization reaction yielding tetrachlorothiophene. The yield improvement is 50–60% more compared to original yield. The distillate crystallization in methanol yielded >98% pure compound compared to typical 90–92% in conventional process. The proposed reaction uses reusable silica-coated 40 nm size magnetic nanoparticles and the catalyst itself is of low cost and reaction conditions are mild. Abstract :